2008
DOI: 10.2175/193864708790894197
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Electrical Conductivity Control at an Industrial Wastewater Treatment Plant

Abstract: Tests were conducted to determine the feasibility for using nitrification and denitrification to control electrical conductivity in an industrial wastewater treatment process effluent. A laboratory-scale sequencing-batch reactor (SBR) system provided 98.5% COD removal and 99.5% nitrification when operating at a solids retention time of 12 days. The resulting average effluent COD concentration was 20 mg/L. Complete nitrification occurred within six hours of aeration but twelve hours of reaction time was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…An internal model developed from referenced sources was used to assess the SBR requirements using information from treatability studies (EPA, 1993;M&E, 2003). Treatability studies confirmed the ability to achieve 98.5% COD removal efficiency and produce an effluent COD concentration of 20 mg/L (Young, et al, 2008). Additionally, nitrification was nearly complete (99.5%) resulting in an effluent quality with an NH 3 -N concentration < 1.0 mg/L.…”
Section: Secondary Biological Treatmentmentioning
confidence: 60%
See 4 more Smart Citations
“…An internal model developed from referenced sources was used to assess the SBR requirements using information from treatability studies (EPA, 1993;M&E, 2003). Treatability studies confirmed the ability to achieve 98.5% COD removal efficiency and produce an effluent COD concentration of 20 mg/L (Young, et al, 2008). Additionally, nitrification was nearly complete (99.5%) resulting in an effluent quality with an NH 3 -N concentration < 1.0 mg/L.…”
Section: Secondary Biological Treatmentmentioning
confidence: 60%
“…Multiple studies were performed to evaluate the efficacy of using the existing anaerobic pretreatment units, evaluate the first stage aerated lagoon performance, quantify denitrification rate parameters and evaluate EC control alternatives (Young et al, 2008). The process flow sheet adopted for the facility is shown in Figure 2.…”
Section: Expanded Treatment Facilitymentioning
confidence: 99%
See 3 more Smart Citations